Effect of Individualized Progesterone Supplementation for Luteal Support in Frozen-Thawed Cycles on Pregnancy Outcomes - Gulsen Dogan Durdag; Gizem Bektas; Esengul Turkyilmaz; Halime Goktepe; Meltem Sonmezer; Yavuz Emre Sukur; Batuhan Ozmen; Cem Atabekoglu; Murat Sonmezer (Gynecology Obstetrics & Reproductive Medicine)
Objective: In frozen-thawed embryo transfer (FET) cycles, preparing a synchronous endometrium for the embryo is essential. Aim of this study is to provide individualized luteal support in hormonally replaced FET cycles, and to evaluate mid-luteal serum progesterone levels and pregnancy outcomes.